Environmental Damage and the Mismeasure of Poverty and Inequality: Applications to Indonesia and the Philippines - Mariano Torras (Asian Development Review, 2002)
Environmental and natural resource accounting has heretofore mostly been conducted in a national income accounting context. Yet income inequality and poverty statistics are often exceedingly optimistic absent an adequate accounting of environmental losses. Following Khan’s study on Bangladesh (1997), this paper adjusts for inequality and poverty measures to account for estimated environmental damage, in this case for Indonesia and the Philippines. Unlike Khan, the paper uses actual data on environmental losses published by the World Resources Institute, and tests for different assumptions regarding the within-population distribution of the environmental damage. Results show that both Gini coefficients and poverty rates increase in each country after the adjustments. The study provides further evidence that growth in gross domestic product (GDP) is not always an adequate poverty reduction measure and, more importantly, calls into question the so-called “environment–equity trade-off”, implying that pro-environment policies have the potential to produce “win-win” outcomes in less developed countries such as Indonesia and the Philippines.